ANALYSIS OF THE USE OF L2TP AND SSTP VPNS DURING THE COVID-19 PANDEMIC - Haeruddin Haeruddin; Kelvin Kelvin (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
COVID-19 is a virus have developed into a global pandemic. This has resulted in millions of employees around the world currently working from home. Virtual Private Network (VPN) can be used to provide employees access to office data from home. This study analyzes the differences between L2TP/IPsec and SSTP VPN protocols to choose a VPN technology that is suitable for use according to user needs. This is done by building the VPN network in according to the device requirements, QoS, security, and scalability parameters using Network Development Life Cycle (NDLC) method. The results of this study indicate that both types of VPNs have their respective advantages and disadvantages in terms of performance, security and scalability. The results of this study are expected to provide an overview for users to consider the type of VPN that suits their needs.